Menu Close

Question-214645




Question Number 214645 by efronzo1 last updated on 14/Dec/24
Answered by golsendro last updated on 15/Dec/24
 = lim_(x→1)  (((√(4−3x))−1)/( (√(1/(3−2x)))−1))     = lim_(x→1)  (((√(4−3x))−1)/(1−(√(3−2x)))) . (√(3−2x))    = 1. lim_(x→1)  ((3−3x)/(2x−2)) . ((1+(√(3−2x)))/( (√(4−3x))+1))    = −(3/2)
$$\:=\:\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\:\frac{\sqrt{\mathrm{4}−\mathrm{3x}}−\mathrm{1}}{\:\sqrt{\frac{\mathrm{1}}{\mathrm{3}−\mathrm{2x}}}−\mathrm{1}}\: \\ $$$$\:\:=\:\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\:\frac{\sqrt{\mathrm{4}−\mathrm{3x}}−\mathrm{1}}{\mathrm{1}−\sqrt{\mathrm{3}−\mathrm{2x}}}\:.\:\sqrt{\mathrm{3}−\mathrm{2x}} \\ $$$$\:\:=\:\mathrm{1}.\:\underset{{x}\rightarrow\mathrm{1}} {\mathrm{lim}}\:\frac{\mathrm{3}−\mathrm{3x}}{\mathrm{2x}−\mathrm{2}}\:.\:\frac{\mathrm{1}+\sqrt{\mathrm{3}−\mathrm{2x}}}{\:\sqrt{\mathrm{4}−\mathrm{3x}}+\mathrm{1}} \\ $$$$\:\:=\:−\frac{\mathrm{3}}{\mathrm{2}} \\ $$

Leave a Reply

Your email address will not be published. Required fields are marked *